Axial vibration mode of coupled liquid-structure-gas system in a rigid cylindrical container - Zainulabidin, Muhd Hafeez; Gorman, D. G. (International Journals of Engineering and Sciences Publisher, 2014)
This paper describes the axial vibration analysis of a closed ends rigid cylindrical container containing liquid and gas which separated by a thin circular plate at their interface. The liquid depths inside the container were varied and then the mode of vibration and the natural frequencies were analyzed. The natural frequencies obtained experimentally were compared favorably with those of commercial finite element analysis software, ANSYS. The vibration mode of the liquid-structure interaction of the tank system can be visualized from the software post processing animation/plot. The visualized modes are also consistent with the measurement by the respective experimental transducers. It was found that strong coupling predominantly occur between liquid and structure. In weak coupling conditions, the modes are predominantly gas mode